INTEGRATING QUR'ANIC ECO-THEOLOGY INTO ISLAMIC EDUCATION: PROMOTING ENVIRONMENTAL AND SOCIAL JUSTICE FOR SUSTAINABLE DEVELOPMENT - Waheeda Waheeda; Subaiki Ikhwan (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The global ecological crisis requires a holistic response that extends beyond technical and policy-based solutions to encompass ethical, spiritual, and educational dimensions. This article examines the epistemological contribution of Islamic eco-theology, particularly through a Qur’anic perspective, in shaping an educational paradigm that promotes environmental sustainability and social justice. This study employs a qualitative library research method, drawing upon Qur’anic verses, Prophetic traditions (hadith), and contemporary literature on Education for Sustainable Development (ESD). The findings reveal that the Qur’anic concepts of khalīfah (stewardship), amānah (trust), and ‘adl (justice) provide a comprehensive ethical framework for fostering ecological responsibility and social equity within Islamic education. These principles encourage a holistic understanding of the relationship between humans, society, and nature, thereby challenging anthropocentric approaches to development. Furthermore, the study demonstrates that Islamic eco-theology enriches the discourse of Education for Sustainable Development by integrating spiritual and theological dimensions that are often overlooked in contemporary sustainability frameworks. The study argues that incorporating Qur’anic eco-theological values into Islamic educational curricula can facilitate a paradigm shift from anthropocentrism toward a cosmocentric and justice-oriented worldview. This transformation has significant implications for educational practice, including the development of integrative curricula that connect environmental education, Islamic philanthropy (zakat, infaq, and waqf), and sustainability values in both formal and non-formal educational settings. Such an approach can contribute to nurturing environmentally responsible and socially conscious citizens capable of addressing contemporary ecological challenges.